Impact of school variables on university performance IMPACTO DE LAS VARIABLES ESCOLARES EN EL RENDIMIENTO UNIVERSITARIO - Mendez Romero, Ricardo Antonio; Donetch Ulloa, Maria Cristina; Garrido Suazo, Claudio (My University, 2022)
The objective of this research was to determine the predictive level of the techni-cal-teaching factors of secondary education in academic success in a Chilean state university, disaggregated into three variants: time of graduation, academic performance and graduate-dropout ratio of each career. Methodologically, a descriptive and correlational analysis is carried out, applying regression models. The school of origin, the educational modality and the grade point average were considered as technical-teaching factors. The results indicate that there is a low correlation between the predictor variables and university performance and the regression analyzes show a low predictive level of the predictor variables.
Keywords: academic performance; college success; dropout rate; graduation rate; logistic regression; regression analysis; retention rate